Synthesis, Features and Solar-Light-Driven Photocatalytic Activity of TiO2 Nanotube Arrays Loaded with SnO2 - Sim, L.C.; Ng, K.W.; Ibrahim, Shaliza; Saravanan, P. (American Scientific Publishers, 2014)
In the present study TiO2 nanotube arrays (TNTs) were loaded with a post-transition metal oxide particles namely SnO2 via incipient wet impregnation method by varying its concentration (1.59 wt%, 2.25 wt% and 2.84 wt%). The photocatalytic activity of the prepared photocatalyst was evaluated for the degradation of methylene blue (MB) in presence of natural solar light irradiation. The morphological analyses revealed that the prepared TNTs had average inner diameter of 109 nm, wall thickness of 15 nm and tube length of 7–10 μm, respectively, while the crystalline phase and raman spectra confirmed the 100% anatase mineral form of TiO2. Further, the presence of SnO2 in TNTs was confirmed by high resolution transmission electron microscopy (HRTEM) and X-ray photoelectron spectroscopy (XPS). The visible light absorption properties of TNTs improved drastically with increasing SnO2 loadings. The coupling effect of SnO2 and TiO2 significantly enhanced degradation efficiency of MB. An 84% degradation of MB was achieved in 6 h of irradiation under clear sky condition.